The Hippocampus and Imagining the Future: Where Do We Stand? - Addis, Donna Rose; Schacter, Daniel (Frontiers in Human Neuroscience, 2012)
Recent neuroimaging work has demonstrated that the hippocampus is engaged when imagining the future, in some cases more than when remembering the past. It is possible that this hippocampal activation reflects recombining details into coherent scenarios, and/or the encoding of these scenarios into memory for later use. However, inconsistent findings have emerged from recent studies of future simulation in patients with memory loss and hippocampal damage. Thus, it remains an open question as to whether the hippocampus is necessary for future simulation. In this review, we consider the findings from patient studies and the neuroimaging literature with respect to a new framework that highlights three component processes of simulation: accessing episodic details, recombining details, and encoding simulations. We attempt to reconcile these discrepancies between neuroimaging and patient studies by suggesting that different component processes of future simulation may be differentially affected by hippocampal damage.